Strategi Kampanye K3 Nelayan Oleh Dinas Kelautan dan Perikanan Jawa Timur di Pantai Popoh Tulungagung - Radja Khais Dewangga; Julyanto Ekantoro; Tira Fitriawardhani (CV. ITTC INDONESIA, 2026)
This study aims to analyze and describe the Fishermen's Occupational Health and Safety (K3) campaign strategies implemented by the Department of Marine Affairs and Fisheries (DKP) of East Java Province at the Popoh Coastal Fishing Port (PPP), Tulungagung. The location was selected based on the geographical characteristics of Popoh Beach, which directly faces the extreme waves of the Indian Ocean, and the high rate of maritime accidents in the area, such as vessels drifting due to bad weather and broken anchor lines. The research method employed is qualitative with a descriptive-evaluative approach. Data were collected through field observations, documentation, and in-depth interviews with key informants from Department of Marine Affairs and Fisheries East Java and fishermen as the primary subjects. Data analysis followed the Miles and Huberman iterative model, which includes data reduction, data display, and conclusion drawing. The results indicate that Department of Marine Affairs and Fisheries East Java implemented a holistic campaign strategy combining face-to-face approaches (informal socialization at the fish auction site), practical skill training (Man Overboard and First Aid simulations), and the utilization of digital media (WhatsApp and TikTok). Beyond education, this strategy was strengthened by providing safety facilities, such as the distribution of Personal Protective Equipment (PPE) including life jackets and anti-slip boots, as well as seaworthiness inspections by the Port Master (Syahbandar). Although the strategy successfully improved the fishermen's cognitive knowledge, the study identified a major obstacle in sociocultural factors: a negligent attitude toward safety and the fatalistic views of traditional fishermen. However, there is a positive shift with the formation of the Fishermen’s Occupational Health and Safety Working Group as a community-level agent of change, ensuring the sustainability of an independent safety culture.